Community Empowerment Through Digital Marketing Training on Processed Chili Powder in Jipurapah Village - Alfina Syntiasari; Cindy Khoirun Nisak; Elsa Auliasandi ikhsan Putri; Ineztasya Eka Rahmadani; Guntum Budi Prasetyo; Kahan Tony Hendrawan (GANDRUNG: Jurnal Pengabdian Kepada Masyarakat, 2023)
Most of the potential or natural products in Jipurapah village come from rice fields and plantations. Rice fields and plantations in Jipurapah village are mostly planted with rice, tobacco, corn, and cayenne pepper. In Jipurapah village most of the natural products are chilies, but during certain weather, the natural products in the form of chilies sometimes experience a decrease due to Patek pest attacks. Based on this, KKN students took the initiative to conduct training on making chili powder for the local people of Jipurapah village to solve the problem. With chili powder-making skills training, the public can sell it and carry out product marketing in the market place which aims to reach a wider market throughout the region where group 2 Community Service Students at STKIP PGRI Jombang choose the Shopee application. The method used is by holding Digital Marketing socialization and chili powder training in Jipurapah village. The conclusions that can be drawn from this community service activity are as follows, namely, Socialization and training activities for making processed chili powder and marketing it through digital marketing have been successfully carried out and can be quickly adopted by the training participants, in this case, the PKK Jipurapah village.